2012
DOI: 10.1089/apc.2012.0169
|View full text |Cite
|
Sign up to set email alerts
|

Drug–Drug Interactions Between Antiretroviral and Immunosuppressive Agents in HIV-Infected Patients After Solid Organ Transplantation: A Review

Abstract: Since the introduction of combination antiretroviral therapy (cART) resulting in the prolonged survival of HIV-infected patients, HIV infection is no longer considered to be a contraindication for solid organ transplantation (SOT). The combined management of antiretroviral and immunosuppressive therapy proved to be extremely challenging, as witnessed by high rates of allograft rejection and drug toxicity, but the profound drug-drug interactions between immunosuppressants and cART, especially protease inhibitor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
64
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(66 citation statements)
references
References 79 publications
0
64
1
Order By: Relevance
“…In our patients on ritonavircontaining cART, the median advised loading and maintenance dose were 2.0 mg and 0.5 mg every 48 hours respectively, which is in agreement with the results from a other cohorts and case reports of posttransplantation HIV-infected recipients on PI-based cART previously described. (12,13). Furthermore, from the simulation of the pharmacokinetic curves as displayed by Figure 2, it can be concluded that patients on ritonavir-boosted cART the initial dose of tacrolimus needs to be strongly reduced to approximately 2 mg (0.025 mg/kg total body weight) in our population to reach therapeutic levels directly posttransplantation.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…In our patients on ritonavircontaining cART, the median advised loading and maintenance dose were 2.0 mg and 0.5 mg every 48 hours respectively, which is in agreement with the results from a other cohorts and case reports of posttransplantation HIV-infected recipients on PI-based cART previously described. (12,13). Furthermore, from the simulation of the pharmacokinetic curves as displayed by Figure 2, it can be concluded that patients on ritonavir-boosted cART the initial dose of tacrolimus needs to be strongly reduced to approximately 2 mg (0.025 mg/kg total body weight) in our population to reach therapeutic levels directly posttransplantation.…”
Section: Discussionmentioning
confidence: 97%
“…Tacrolimus is primarily metabolized by cytochrome (CYP) 3A in the liver and a substrate of P-glycoprotein (Pgp), an efflux pump, which is primarily localized in the liver and intestines (10,11). Many of the drugs included in cART have been reported to show clinically relevant interactions with CNIs (12). For instance, nonnucleoside reverse transcriptase inhibitors (NNRTIs) are well-known inducers of CYP3A enzymes that may affect tacrolimus pharmacokinetics and can cause underexposure but also have an overlapping iatrogenic profile regarding hepatoxiticity (13).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…With the inhibition of the CYP3A enzyme system, tacrolimus was recommended at 0.5 to 1 mg weekly to achieve a trough level of 8 to 12 ng/mL. [12][13][14][15] In conclusion, transplant is the best replacement therapy in HIV-positive end-stage kidney disease patients with controlled AIDS management under highly active antiretroviral therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Another possible explanation for higher rejection rates is inadequate immunosuppression. Calcineurin inhibitors (CNIs) are administered less frequently in HIV-infected kidney transplant recipients because of drug-drug interaction with protease inhibitors (PIs), which potently inhibit the cytochrome p-450 3A4 system [7]. One of our patients was only on 0.125mg of tarcolimus every other day compared to a total daily dose of 4–6 mg, which is normally used in non-HIV patients.…”
Section: Discussionmentioning
confidence: 99%